Implementasi Manajemen Strategik Pada Bidang Pendidikan Dalam Perspektif Sumber Daya Manusia, Operasional, Anggaran, Dan Administrasi - Gunawan Aji; Fiinaa Maghfirotuzzahro; Giating Khoiriamal; Ulfa Munawaroh; Mia Amelia Zahra (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Advancements in educational world make the responsibility of educational institutions in generating graduates with better quality to be able of facing competition of human life in the future. To improve the quality of education, directed strategic efforts are needed in utilizing existing resource opportunities. The implementation of management related to human resources, operations, finance or budget, and administration is very important in formal and non-formal educational institutions. This research aims to reveal the strategic management implemented in educational institutions in improving education’s quality. This research uses a descriptive qualitative method of literature study type with data sources obtained from several journal articles. This research has the results that the programs in improving human resources are the recruitment process, coaching and empowerment of educators. In the management of operations in educational institutions, it is carried out by concentrating the implementation of learning programs and encouraging the growth of community awareness to create community learning activity centers. The budget also supports the implementation of educational programs, so it is important to manage finances and budgets so that educational institutions can operate effectively. Meanwhile, in improving administrative services, it is conducted by strategy formulation, strategy implementation, strategy planning and control, and evaluation.